2010
DOI: 10.4081/ijas.2010.e55
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of caseins, estrogen and prolactin receptors in mammary glands of dairy ewes

Abstract: In this study, we analyzed the developmental expression of estrogen receptors (ESR1 and ESR2), prolactin receptors (PRLR) and casein genes (CSN1S1, CSN1S2, CSN2 and CSN3) in the ewe mammary glands from prepubertal stage to involution. Using Real-time PCR we showed that the activation of casein genes transcription was up regulated during lactation and significantly down regulated before lambing and at involution in comparison to the expression measured in the prepubertal group. The highest expression of ESR1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
7
10
0
Order By: Relevance
“…In contrast to our findings in lactating cows, the relative expression level of LALBA in ewes reached the highest value only at the end of lactation. Furthermore, Colitti and Pulina (2010) analyzed transcripts of the four caseins CSN1S1, CSN1S2, CSN2, and CSN3 in mammary tissue after slaughter in dairy ewes. Respective to the study of Colitti and Pulina (2010), gene expression of the four caseins was up-regulated during peak, mid-, and late lactation but down-regulated during pregnancy and involution.…”
Section: Milk Protein Gene Expressionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to our findings in lactating cows, the relative expression level of LALBA in ewes reached the highest value only at the end of lactation. Furthermore, Colitti and Pulina (2010) analyzed transcripts of the four caseins CSN1S1, CSN1S2, CSN2, and CSN3 in mammary tissue after slaughter in dairy ewes. Respective to the study of Colitti and Pulina (2010), gene expression of the four caseins was up-regulated during peak, mid-, and late lactation but down-regulated during pregnancy and involution.…”
Section: Milk Protein Gene Expressionmentioning
confidence: 99%
“…Furthermore, Colitti and Pulina (2010) analyzed transcripts of the four caseins CSN1S1, CSN1S2, CSN2, and CSN3 in mammary tissue after slaughter in dairy ewes. Respective to the study of Colitti and Pulina (2010), gene expression of the four caseins was up-regulated during peak, mid-, and late lactation but down-regulated during pregnancy and involution. Those findings correspond to ovine milk protein composition during lactation.…”
Section: Milk Protein Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Bionaz and Loor () found that the CSN3 gene expression pattern was more or less similar to the lactation curve in the MT of cows. On the other hand, Colitti and Pulina () observed no differences on the expression of caseins' genes in dairy ewes among 30, 60 and 150 DIM, when took MT samples from different animals throughout the lactation period. Additionally, Colitti and Farinacci (), by taking MT from different ewes too, found that the expression of LALBA gene reached the highest value at the end of lactation (150 DIM).…”
Section: Discussionmentioning
confidence: 96%